Effect of Endogenous Lipids and Proteins on the Antioxidant, in vitro Starch Digestibility, and Pasting Properties of Sorghum Flour - Irondi, Emmanuel Anyachukwu; Adewuyi, Adekemi Esther; Aroyehun, Tolulope Muktar (Frontiers in Nutrition, 2022)
This study evaluated the effect of endogenous lipids and proteins on the antioxidants, starch digestibility and pasting properties of sorghum (Sorghum bicolor) flour (SF). Endogenous lipids and/or proteins were removed from different portions of SF to obtain defatted (DF), deproteinized (DP), and defatted and deproteinized (DF-DP) flours. Bioactive constituents (total phenolics, tannins, flavonoids, saponins and anthocyanins), antioxidant activities (ABTS*+ and DPPH* scavenging activities, reducing power and Fe2+ chelating capacity), starch, amylose, starch hydrolysis index (HI), estimated glycaemic index (eGI) and pasting properties of treated and control (untreated) flours were determined. The control flour (SF) had significantly higher (p < 0.05) levels of all the bioactive constituents and antioxidant activity tested than the DF, DP, and DF-DP flours; with the DF-DP flour having the least bioactive constituents’ levels and antioxidant activity. In contrast, the starch, amylose, HI and eGI were consistently in the order of DF-DP > DF > DP > control flour (p < 0.05). The control flour had the highest (p < 0.05) peak viscosity, and the least peak time and pasting temperature; while the DF flour had the highest final viscosity. Therefore, endogenous lipids and proteins contribute to the antioxidant, starch digestibility and pasting properties of sorghum flour.